Bi(o)communications among peripheral blood fractions: A focus on NK and NKT cell biology in rheumatoid arthritis. (June 2013) - Aggarwal, Ashish; Sharma, Aman; Bhatnagar, Archana
<x xml:space="preserve">Abstract</x> Rheumatoid Arthritis (RA) is an autoimmune disease with unknown pathophysiology involving many interwoven signalling cascades. ROS, NK and NKT cells might be crucial in the disease severity of RA of which the role of NK and NKT cells are controversial in literature. However, the role of oxidative stress, its impact on NK and NKT cell immunobiology and disease activity (DAS28) is largely unknown. Therefore, we studied the role of oxidative stress and NK cell subsets in the pathogenesis of RA. The state of oxidative stress in various peripheral blood fractions, percentage NK and NKT cell expression, their altered apoptotic signaling pathways involving mitochondrial membrane potential, FAS associated death domain (FADD) mediated pathways and DNA damage were analyzed. Results indicated a state of profound oxidative stress in the peripheral blood of RA patients where percentage of NK and NKT cell subsets diminished while ROS levels increased. The depolarized mitochondrial membrane potential, FAS, FASL and active caspase-3 positive NK and NKT cell subsets were considerably elevated in patients. The DNA damage, assessed as percentage of DNA in comet tail, was significantly elevated. Findings of the present work indicate increased apoptosis of peripheral NK and NKT cells in the diseased condition. PBMC and RBC are the major sites of enhanced oxidative stress. The state of oxidative stress and altered immunobiology of NK and NKT cells strongly correlated with Disease activity score. The present study strongly supports the protective role of NK cell subsets in the pathogenesis of RA.